The use of targeted angiogenic therapies for ischemic diabetic foot ulcer repair. - Fatigracy Maria dos Santos de Canha (2022)
Diabetes Mellitus is a metabolic disease that has a high prevalence worldwide and is characterized by chronic hyperglycemia leading to the development of complications. In particular, it is these complications that result in huge mortality rates in diabetic patients. This work focuses on diabetic foot ulcers (DFUs), which are one of the most common complications of type 2 diabetes mellitus (T2DM) and cause significant morbidity, mortality, and healthcare costs. The healing of DFUs is hindered by deregulation of nearly all phases of this process due to the hyperglycemic environment. Although therapies currently exist to treat a patient with DFU, they are proving inadequate. In the present work, angiogenesis is highlighted as part of the proliferative phase, which, when diminished, plays an important role in the impaired healing of DFU and other chronic wounds. Therefore, the search for new therapeutic strategies targeting angiogenesis is of great interest. Here, we provide an overview of molecular targets with therapeutic potential and therapies that act on angiogenesis. To this end, a search of papers from the PubMed and Scopus databases from 2018 to 2021 was performed to review angiogenesis as a therapeutic target for DFU. Growth factors, microRNAs, and signaling pathways were investigated as molecular targets, and negative pressure, hyperbaric oxygen therapy, and the use of nanomedicine were explored as therapies.